PERILAKU TEKUK (BUCKLING) PADA BAMBU PETUNG BENTUK BILAH - AGUSTIN GUNAWAN (Inersia: Jurnal Teknik Sipil, 2018)
The Compressed bar at the frame, columns, and other structures is always probably happened buckling. The experiment is conducted to investigate the behavior of buckling at the bar of lath shaped bamboo petung and the buckling strength of  the experiment result with the theory result (the equation of tetmayer and euler, proposal of morisco, and atrops (D/T=0)). In the research, it is conducted testing of the mechanic character of bamboo and wood specimens, testing of resin, and buckling testing  with the compressed testing principle. The testing result showed that buckling happened at the lath shaped bamboo petung is influenced by the length of bar, the resin strength, and the quality of work.   The buckling stress of the experiment result was higher than  the result of  morisco proposal, but it’s less than the result of tetmayer and atrops (D/T=0), so that  the equation of  morisco proposal is safe to used at the compressed bar design.